2017
DOI: 10.1038/ismej.2017.43
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial carbon use plasticity, phylogenetic diversity and the priming of soil organic matter

Abstract: Microorganisms perform most decomposition on Earth, mediating carbon (C) loss from ecosystems, and thereby influencing climate. Yet, how variation in the identity and composition of microbial communities influences ecosystem C balance is far from clear. Using quantitative stable isotope probing of DNA, we show how individual bacterial taxa influence soil C cycling following the addition of labile C (glucose). Specifically, we show that increased decomposition of soil C in response to added glucose (positive pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 129 publications
(76 citation statements)
references
References 62 publications
4
71
1
Order By: Relevance
“…) and that the enigmatic phenomenon of priming—in which pulses of new organic matter enhance the decomposition of older organic matter—is mediated by taxa across the phylogenetic spectrum (Morrissey et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…) and that the enigmatic phenomenon of priming—in which pulses of new organic matter enhance the decomposition of older organic matter—is mediated by taxa across the phylogenetic spectrum (Morrissey et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the ability to link population dynamics of individual microbial taxa to biogeochemical processes might illuminate whether a handful of hyper-abundant foundation taxa (Ellison et al 2005) drive element fluxes, or whether they are instead regulated by rare keystone taxa (Power et al 1996). Applications of qSIP in this vein have already revealed that microbial activity varies with phylogeny ) and that the enigmatic phenomenon of priming-in which pulses of new organic matter enhance the decomposition of older organic matter-is mediated by taxa across the phylogenetic spectrum (Morrissey et al 2017).…”
Section: 5mentioning
confidence: 99%
“…The increasing priming effect of aboveground litterfall with experimental duration concurs with those from rhizosphere (Huo et al., ). One possible mechanism for this enhancement is that soil microbial community composition changes in concert with its C use (Morrissey et al., ). Microorganisms prefer to use fresh plant litter as a growth substrate at the beginning of fresh C addition, resulting in no or even negative priming effects; however, long‐term C substrate addition would trigger the production of enzymes that are in favour of priming the native soil C (Morrissey et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…One possible mechanism for this enhancement is that soil microbial community composition changes in concert with its C use (Morrissey et al., ). Microorganisms prefer to use fresh plant litter as a growth substrate at the beginning of fresh C addition, resulting in no or even negative priming effects; however, long‐term C substrate addition would trigger the production of enzymes that are in favour of priming the native soil C (Morrissey et al., ). Alternatively, the initial weak response in priming effect could result from the disturbance of experimental establishment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation